The use of an online support group for neuromuscular disorders: a thematic analysis of message postings - Meade, Oonagh; Buchanan, Heather; Coulson, Neil S. (Taylor & Francis, 2017)
Purpose: People affected by neuromuscular disorders can experience adverse psychosocial consequences and difficulties accessing information and support. Online support groups provide new opportunities for peer support. The aim of this study was to understand how contributors used the message board function of a newly-available neuromuscular disorders online support group. Methods: Message postings (n=1,951) from the first five months of the message board of a newly-formed online support group for neuromuscular disorders hosted by a charitable organisation were analysed using inductive thematic analysis. Results: Members created a sense of community through disclosing personal information, connecting with people with similar illness experiences or interests, welcoming others, and sharing aspirations for the development of a resourceful community. Experiences, emotional reactions and support were shared in relation to: delayed diagnosis; symptom interpretation; illness management and progression; the isolating impact of rare disorders; and the influence of social and political factors on illness experiences. Conclusions: This study provided a novel insight into individuals’ experiences of accessing a newly-available online support group for rare conditions hosted by a charitable organisation. The findings highlight how the online support group provided an important peer support environment for members to connect with others, exchange information and support, and engender discussion on political and social issues unique to living with often-rare neuromuscular disorders. Online support groups may therefore provide an important and easily accessible support outlet for people with neuromuscular disorders as well as a platform for empowering members to raise awareness about the impact of living with these conditions. Further research is needed to examine member motivations for using such groups and any effects of participation in greater detail.